Exploring unusual temperature-dependent optical properties of graphite single crystal by spectroscopic ellipsometry. (September 2022) - Gulo, Desman Perdamaian; Hung, Nguyen Tuan; Yang, Tan-Ju; Shu, Guo-Jiun; Saito, Riichiro; Liu, Hsiang-Lin
Abstract: This study investigated the optical properties of graphite single crystal as a function of temperature between 4.5 and 500 K and within the spectral range of 0.73–6.42 eV through spectroscopic ellipsometry. At room temperature, the complex dielectric function of graphite exhibited broad spectra in the ultraviolet energy region. The Breit–Wigner–Fano (BWF) line shape analysis of the optical absorption spectrum demonstrated that two BWF line shapes were fitted with central energies at 4.85 ± 0.01 eV and 6.21 ± 0.03 eV. These two features were attributed to interference between an excitonic transition at the saddle point (M) in the band structures and collective excitations of the surface plasmons. Analysis of the temperature-dependent asymmetric BWF line shape indicated that the peak position shifted to lower energies under increasing temperatures, with the linewidth becoming narrow and the intensity increasing; this can be explained by the asymmetric factor 1/ q BWF, which decreased under increasing temperatures. The temperature dependence of optical absorption for graphite is opposite to that of the interband absorptions observed in silicon. First-principles calculations verified the presence of two resonant conditions in the ultraviolet energy region. The lifetime of surface plasmons was expected to decrease with increased temperatures, leading to a decrease of the 1/ q BWF. These results offer insight into quasiparticle band structures and collective excitations of graphite and provide valuable information for the technological development of graphite-based ultraviolet optoelectronic and photonic devices at different temperatures. Graphical abstract: Image 1